Selective laser trabeculoplasty versus topical medication as initial glaucoma treatment: the glaucoma initial treatment study randomised clinical trial. Issue 6 (5th September 2019) - Ang, Ghee Soon; Fenwick, Eva K; Constantinou, Marios; Gan, Alfred Tau Liang; Man, Ryan Eyn Kidd; Casson, Robert J; Finkelstein, Eric A; Goldberg, Ivan; Healey, Paul R; Pesudovs, Konrad; Sanmugasundram, Sutha; Xie, Jing; et al.
Abstract : Background/Aims: To determine if selective laser trabeculoplasty (SLT) is superior to topical medication as a first-line treatment for glaucoma on quality of life (QoL) and clinical outcomes. Methods: In this international, longitudinal, multisite randomised controlled trial, treatment naïve mild-to-moderate primary open angle or exfoliation glaucoma patients were randomised 1:1 to SLT or topical medication. Glaucoma-specific QoL (primary outcome) was measured using the Glaucoma Outcomes Assessment Tool (GOAT; 342 items, 12 domains). Secondary outcomes included rate of successful intraocular pressure (IOP) reduction (>25% reduction from baseline) and presence of ocular surface disease including conjunctival hyperaemia and eyelid erythema. Our intention-to-treat analysis was performed at months 12 and 24. Results: Of 167 enrolled patients, 83 and 84 were randomised to SLT and topical medication, respectively; and 145 (n=75 SLT, n=70 medication) completed 24-month follow-up. While both treatment arms achieved significant within-group gains in GOAT outcomes at both endpoints, SLT patients reported a greater between-group improvement in 'social well-being' compared with medication patients (mean±SE=0.28±0.13; p=0.034) at 24 months. At month 24, the rate of successful IOP reduction was 18.6% (95% CI 3.0% to 34.3%, p=0.022) higher (absolute difference) in the medication compared with SLT group. More individuals in the medication group had conjunctival hyperaemia and eyelid erythema compared with SLT at 24 months. Conclusion: Overall, we did not find evidence that SLT was superior to medication in improving glaucoma-specific QoL. While we found superior IOP reduction in the medication arm, eyelid erythema and conjunctival hyperaemia were more prevalent in these patients compared with the SLT group. Trial registration: ACTRN12611000720910.